A Study on the Effect of Environmetal Conditions on the Data Quality of Scanned Images Collected from the 3D Human Body Light Scanners - Nguyen, Thi Nhung; Phan, Thanh Thao (Old Journal, 2020)
This article presents the results of the study on the influence of environmental conditions on the quality of human body scan images collected from 3D scanners using structured light with impact factors including: the scanning distance, backdrop color and environmental light intensity. In this paper, we used Meshlab software for image grading. We also used grayscale valueof Histogram diagram and thenumber of 3D scanned pixels which are determined to evaluate the data quality collected from the 3D human body light scanners. In addition, the study used Design Expert 6.0 software for analyzing collected data and checked the effect of those factors. The experimental results are given to clarify the effect of considered factors.